Flood Vulnerability Index for Critical Infrastructure Towards Flood Risk Management - Nicole Lee Siew Len; Nurmin Bolong; Rodeano Roslee; Felix Tongkul; Abdul Karim bin Mirasa; Janice Lynn Ayog (2018)
In the recent years, the impacts of floods have gained importance because of the increasing number of people who are affected by its adverse effects. Flood destroyed critical infrastructures that are needed as shelter and also emergency relief for victim. In order to provide a better understanding of flood risk management, a review of current practice in flood risk management and flood vulnerability index was carried out.